Changes in HIV incidence during the COVID-19 pandemic (2020–22) compared with the pre-pandemic period (2015–19) in Peru: An observational study - Max Carlos Ramírez-Soto; Hugo Arroyo-Hernández (PLoS ONE, 2025)
Introduction During the COVID-19 pandemic, non-pharmaceutical interventions affected the screening of sexually transmitted infections. We investigated the incidence of HIV infection during the COVID-19 pandemic compared with incidence in the pre-pandemic period. Methods In this observational study, we analyzed HIV surveillance data for all age-groups from 25 geographically diverse regions in Peru from Jan 1, 2015 to Dec 31, 2022. HIV incidence during the COVID-19 pandemic (2020, 2021, and 2022) was compared with pre-pandemic rates (2015–19). Results Overall, there were 65,166 new cases of HIV infection from January 1, 2015 to December 31, 2022. HIV incidence risk ratio (IRR) was 26% lower in 2020 (IRR = 0.74; 95% CI, 0.71–0.76), 5% higher in 2021 (IRR = 1.05; 95% CI, 1.02–1.08) and 16% higher in 2022 (IRR = 1.16; CI, 1.13–1.20), compared with the pre-pandemic period. Furthermore, compared with the pre-pandemic period, the annual incidence of HIV among men was 29% lower in 2020 (IRR = 0.71; 95% CI, 0.68–0.73), 4% higher in 2021 (IRR = 1.04, 95% CI, 1.01–1.08) and 10% higher in 2022 (IRR = 1.10; 95% CI, 1.06–1.14). In the age-stratified analysis, the annual HIV incidence in 2020 was 21 and 33% lower for those aged 18–29 (IRR = 0.79; 95% CI, 0.75–0.83) and 30–59 (IRR = 0.67; 95% CI, 0.64–0.70), respectively, compared with the pre-pandemic period. Finally, annual HIV incidence has decreased in 11 out of 25 regions in 2020, compared with the pre-pandemic period. Conclusions Our study showed that during the COVID-19 pandemic in 2020, the incidence of HIV infection in the population of Peru decreased. However, this incidence began to return to pre-pandemic rates in 2021, coinciding with the easing or elimination of non-pharmaceutical interventions. By 2022, the incidence of HIV infection was higher than in the pre-pandemic period, especially in regions of the Peruvian Amazon.